2012
DOI: 10.3109/09286586.2012.718402
|View full text |Cite
|
Sign up to set email alerts
|

Epidemic Adenoviral Keratoconjunctivitis Possibly Related to Ophthalmological Procedures in a Neonatal Intensive Care Unit: Lessons from an Outbreak

Abstract: Ophthalmologic procedures continue to be a potential source of adenovirus outbreaks. However, negligence of contact measures during routine daily nursing care seems to be a more important contributing factor for rapid spread. Strict adherence to appropriate aseptic procedures is required to prevent this potentially hazardous infection in preterm infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 25 publications
1
16
0
1
Order By: Relevance
“…Treatment of surfaces with alcohol solutions (85 to 95%) for at least 2 min or with sodium hypochlorite for 10 min is effective at inactivating the virus (83). Efficient decontamination of surfaces is of paramount importance, particularly in transplant and intensive care units, to prevent this mode of transmission in immunosuppressed patients (84). Although exogenous infection by nosocomial or community acquisition in the inpatient setting is a rather rare cause of HAdV-related diseases, outbreaks of infections on hematology or transplant wards as well as in eye clinics, resulting in closures, have been documented (19,85,86,87).…”
Section: Transmissionmentioning
confidence: 99%
“…Treatment of surfaces with alcohol solutions (85 to 95%) for at least 2 min or with sodium hypochlorite for 10 min is effective at inactivating the virus (83). Efficient decontamination of surfaces is of paramount importance, particularly in transplant and intensive care units, to prevent this mode of transmission in immunosuppressed patients (84). Although exogenous infection by nosocomial or community acquisition in the inpatient setting is a rather rare cause of HAdV-related diseases, outbreaks of infections on hematology or transplant wards as well as in eye clinics, resulting in closures, have been documented (19,85,86,87).…”
Section: Transmissionmentioning
confidence: 99%
“…It has been previously stated that outbreaks of AVC in NICU were commonly manifested after ophthalmological examination procedures due to contaminated instruments [9, 11]. Low BW and patient care factors were also shown to be other causes of conjunctivitis among preterm infants [14].…”
Section: Discussionmentioning
confidence: 99%
“…Various studies reported outbreaks due to adenovirus infections at neonatal intensive care unit (NICU). Also the association between AVC and ROP examinations has been previously published [911]. …”
Section: Introductionmentioning
confidence: 99%
“…Это связано в первую очередь с увеличением число офталь-мологических осмотров и манипуляций при развитии оф-тальмологической службы в перинатальных центрах [6,7]. К сожалению, трудности в изоляции детей, невозмож-ность выписать ребенка на долечивание домой, плохая информированность медицинского персонала о высокой контагиозности инфекции и недостаток знаний о мерах профилактики заболевания, приводит к быстрому рас-пространению инфекции внутри учреждения.…”
unclassified